Calcaneal Quantitative Ultrasound and Bone Turnover Markers for Osteoporosis Screening in Elders, the Providing of Benefits (Asian Journal of Pharmaceutics (AJP), 2019)
Context: Calcaneal quantitative ultrasound (QUS) is attractive as a pre-screening tool for osteoporosis,alternative to dual-energy X-ray absorptiometry. Bone turnover markers (BTMs) are represented as boneformation indicators. QUS and BTM analysis may provide osteoporosis screening and bone turnover status,which provide benefit for osteoporosis management. Aims: The aims of this study were (1) to compare thevalues of bone mineral density (BMD) and BTMs, including N-terminal extension propeptide of type-I collagen,alkaline phosphatase (ALP), C-terminal telopeptide of type-I collagen (CTX), and osteocalcin (OC), and bonerelatingbiochemical parameters, such as 25-hydroxyvitamin D (25(OH)D), calcium, phosphorus and magnesiumbetween osteoporotic, osteopenia, and normal BMD elders and (2) to investigate the relationship between serumBTMs and BMD. Materials and Methods: Determination of BMD, BTMs, and bone-related biochemicalparameters from 150 of the elders at Amphawa District, Sumut Songkhram, was determined by calcaneal QUSand automatic analyzers, respectively. One-way ANOVA was used to compare continuous variables between threeelder groups. Multiple comparisons among groups were used least-significance different. Pearson correlation wasused to evaluate the correlation between BMD and BTMs. The statistical significance was considered at P < 0.05.Results and Discussion: BMD, calcium, phosphorus, and CTX levels were significantly different among threeelder groups. CTX was significantly inversely correlated to BMD. Calcium, phosphorus, and CTX can be usefulwith osteoporosis screening by QUS, especially for osteopenia. Conclusions: Combination of calcaneal QUSand biochemical tests, including serum calcium, phosphorus, and CTX measurement as early diagnosis, providesmore benefits for osteoporosis management and suitable for mass screening and intervention.